An SDN-based algorithm for caching, routing, and load balancing in ICN - Tavasoli, MohammadBagher; Saidi, Hossein; Ghiasian, Ali (China communications, 2024)
One of the challenges of Information-centric Networking (ICN) is finding the optimal location for caching content and processing users' requests. In this paper, we address this challenge by leveraging Software-defined Networking (SDN) for efficient ICN management. To achieve this, we formulate the problem as a mixed-integer nonlinear programming (MINLP) model, incorporating caching, routing, and load balancing decisions. We explore two distinct scenarios to tackle the problem. Firstly, we solve the problem in an offline mode using the GAMS environment, assuming a stable network state to demonstrate the superior performance of the cache-enabled network compared to non-cache networks. Subsequently, we investigate the problem in an online mode where the network state dynamically changes over time. Given the computational complexity associated with MINLP, we propose the software-defined caching, routing, and load balancing (SDCRL) algorithm as an efficient and scalable solution. Our evaluation demonstrates that the SDCRL algorithm significantly reduces computational time while maintaining results that closely resemble those achieved by GAMS.